Open notes in patient care: confining deceptive placebos to the past? - Blease, Charlotte (Journal of medical ethics, 2022)
Increasing numbers of health organisations are offering some or all of their patients access to the visit notes housed in their electronic health records (so-called ‘open notes’). In some countries, including Sweden and the USA, this innovation is advanced with patients using online portals to access their clinical records including the visit summaries written by clinicians. In many countries, patients can legally request copies of their records; however, open notes are different because this innovation offers patients rapid, real-time access via electronic devices. In this brief report, we explore what open notes might mean for placebo use in clinical care. Survey research into patient access to their clinical notes shows that increased transparency enhances patients’ understanding about their medications and augments engagement with their care. We reflect on the consequences of access for placebo prescribing, particularly for the common practice of deceptive placebo use, in which patients are not aware they are being offered a placebo. In addition, we explore how open notes might facilitate placebo and nocebo effects among patients. Bridging placebo studies with medical ethics, we identify a range of empirical research gaps that now warrant further study.